A defect in the PINOID serine/threonine kinase affects leaf shape in cucumber. Issue 9 (9th September 2019) - Mach, Jennifer
Abstract : Leaf shape has important implications for optimizing plant architecture for grain crops and horticultural crops. Examination of the cucumber ( Cucumis sativus L.) round leaf ( rl ) mutant by Song et al. (2019) revealed that the PINOID protein kinase affects leaf shape by altering auxin biosynthesis, transport, and signaling.